Malaysian undergraduate students’ views on English public speaking at university: Their performance, preferred instructor and methods of teaching - Ahmad Taufik Hidayah, Abdullah; Mohd Nazri, Latiff Azmi (2019)
Speaking English language in front of the public is sometimes a daunting task to many people, including students of universities. Those who are capable of delivering a sound presentation in English language will definitely have some advantages for future employment and professions. This research addresses issues related to English public speaking at the university by setting three objectives. Firstly, it seeks undergraduate students’ opinions of their English public speaking performance. Secondly, to get insights on the students’ preferred instructors in teaching English public speaking and thirdly to get their opinions on preferred techniques or methods in teaching English public speaking. This research employed qualitative approach by conducting interviews to 25 students from 9 faculties at Universiti Sultan Zainal Abidin (UniSZA), Malaysia. The findings revealed that majority of the students opined that their performance in English public speaking was rather poor and moderate. Only a small section of students thought that their performance was fairly good. Some contributing factors to the poor performance of their English public speaking were due to lack of confidence, lack of English grammar and vocabularies. It was also revealed that the students preferred having instructors who were friendly, and had a high sense of humor. In relation to teaching methods or techniques, the research revealed that the students preferred to have practices in a nonthreatening environment with some meaningful activities such as video shows, drama, sketch or English games that could stimulate a conducive and fun learning environment.